2005
DOI: 10.1191/0961203305lu2162cr
|View full text |Cite
|
Sign up to set email alerts
|

Can systemic lupus erythematosus be the cause of collapsing glomerulopathy?

Abstract: Collapsing glomerulopathy is a severe form of glomerular injury, closely associated with HIV infection, characterized by the collapsing feature of glomerular damage with frequent tubulointerstitial involvement and rapid progression to terminal renal failure. The etiopathogenesis in non-HIV infected patients remains obscure. We reported a patient whose diagnosis of collapsing glomerulopathy (CG) and systemic lupus erythematosus (SLE) was done simultaneously and described the diseases characteristics suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…To our knowledge there are 4 previous case reports of collapsing glomerulopathy in patients with SLE [2][3][4][5]; the index case is the first paediatric patient to be described. All 4 cases described were in female patients, aged 17-48 years.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge there are 4 previous case reports of collapsing glomerulopathy in patients with SLE [2][3][4][5]; the index case is the first paediatric patient to be described. All 4 cases described were in female patients, aged 17-48 years.…”
Section: Discussionmentioning
confidence: 99%
“…IVIg, intravenous immunoglobulins; CVVH, continuous venovenous hemofiltration; MMF, mycophenolate mofetil. or death during therapy (9)(10)(11)(12)(15)(16)(17)(18). Only 25% progression to ESRD or death in this group is a surprising finding, and it may be related to a shorter follow-up period or less-stringent criteria for the diagnosis of CG.…”
Section: Discussionmentioning
confidence: 92%
“…Anecdotal CG in autoimmune diseases including SLE, SLE-like disease, and mixed connective tissue disease has been previously reported (1,2,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The aim of this study is to report an analysis of the clinicopathologic findings and the possible association of renal lesions with CG in the setting of SLE and lupuslike disease and review the literature of the reported cases.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of the remaining cases of CG in patients with SLE presented by Salvatore et al, as well as in prior reports (8)(9)(10)(11)(12)(13)(14), remains unclear, although it should be noted that the great majority of these patients had active systemic disease (often a lupus flare) and a significant number had concurrent lupus nephritis, albeit usually mild (most often International Society of Nephrology/Renal Pathology Society class II). This certainly suggests involvement of humoral and/or cell-mediated immunity, both of which have been implicated in the pathogenesis of podocytopathies and of SLE (15)(16)(17)(18)(19).…”
mentioning
confidence: 91%
“…Unlike the case with CG in patients with SLE, patients with lupus podocytopathy most often show some therapeutic response to steroids and/or other immunosuppressive therapy and only infrequently progress to ESRD within the first few months to years after biopsy, although the responses are often only partial remissions, even in patients with minimal histologic lesions (8,9,20,21). The relationship between lupus podocytopathy and the CG lesions described by Salvatore et al and others (7)(8)(9)(10)(11)(12)(13)(14) remains unclear, much as is the case with collapsing and noncollapsing forms of idiopathic FSGS, although in all of these lesions the primary target of injury is likely to be the podocyte, and indeed CG may represent an extreme form of lupus podocytopathy.…”
mentioning
confidence: 99%